Design and Diagnostics of Non-Equilibrium Atmospheric Plasma Sources for Cell Treatment and Bacterial Decontamination - Stancampiano, Augusto <1987> (Alma Mater Studiorum - Università di Bologna, 2016)
The dissertation focuses on several aspects of non-equilibrium atmospheric plasma technology, also known as cold atmospheric plasma (CAP) technology, including the design, the diagnostic and the optimization of CAP sources for biomedical applications. The first part of the dissertation concerns the characterization of a single electrode atmospheric pressure plasma jet (APPJ) through various diagnostic techniques, including ICCD and Schlieren high speed imaging. First, the results for the APPJ freely expanding in atmosphere are presented along with the detailed description of the methodology developed for the ICCD analysis of plasma discharges driven by sub-microsecond voltage pulses. Second, results on the investigation on the APPJ source while impinging on a liquid substrate are shown to highlight the influence of the presence of the liquid substrate on the characteristics of the plasma discharge. In the second part of the dissertation focuses on the application of CAP technology in various branches of the medical field. The applications reported in this dissertation include: plasma treatment of soft reline palatal obturators prostheses for bacterial decontamination and reduction of bacteria adhesion; plasma direct and indirect treatment of L5178Y lymphoma cells to investigate the fundamental mechanisms promoting cell death and cell-cycle arrest; plasma treatment of tooth root canal dentin in standard dental procedures for the enhancement of the adhesion of resin composites for dental restorations. Overall, all findings support the feasibility of these plasma applications and help in the understanding of some of their governing mechanisms.